PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN, OUTSIDER OWNERSHIP, DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN: (Studi Empiris Pada Perusahaan Property and Real Estate Yang Terdaftar Di Bursa Efek Indonesia 2016-2019) - Nenik Marianti; Yusralaini, Yusralaini; Julita Julita (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study was to examine the effect of profitability, solvency, firm size, outsider ownership, and auditor’s firm reputation towards timeliness of financial reporting at property and real estate companies listed on the indonesian stock exchange period 2016-2019. The data used in this research ini secondary data, namely from annual financial reports. These samples were obtained by purposive sampling method, using several criteria in order to obtain a sample of 24 companies and measure the timeliness of financial reporting with the dummy variables. Hypothesis testing is done by logistic regression analysis with SPSS ver. 26.0. The result of this research provides evidence that the profitability have a influences on timeliness of financial reporting. However there is no evidence that solvency, firm size, company age, outsider ownership, and auditor’s firm reputation have influence on timeliness of financial reporting.